The Utilisation of Rice Husks as Stand-alone Substrate in the Solid-State Fermentation for Amylase Production by Local Isolate Aspergillus flavus NSH9 - Rosmawati, Saat; Mohd Hasnain, Hussain; Awang Ahmad Sallehin, Awang Husaini (Akademi Sains Malaysia, 2025)
A variety of agro-waste has been applied as the solid-state fermentation (SSF) substrate for the production of amylase, nevertheless, only a few studies of rice husks with supplements used as the substrate were reported. Hence, this study was conducted as to investigate the feasibility of rice husk alone without additional supplements as the SSF substrate to produce amylase from the local fungal isolate. Different microbial strains or isolate with different fermentation substrates may have different SSF process requirement for achieving high enzyme activity yield. Therefore, the SSF parameters such as initial moisture content of the substrate, incubation period, incubation temperature and substrate particle were studied and optimised. The highest amylase enzyme activity was observed at 70 % of initial moisture content, 144 hours (6 days) and 30°C, with substrate particle size of 2 mm. Starch hydrolysis analysis performed indicated that the strength of amylase activity in the partially purified extracted enzyme was three times higher than the crude enzyme. Furthermore, a negligible or none of major aflatoxin compounds was detected in the crude and partially purified enzyme. The obtained findings strongly suggest the high potential usage of rice husk alone as the substrate in the SSF process for the production of aflatoxin-free amylase by the local isolate Aspergillus flavus (A. flavus) NSH9.